Investigation of the Hydrolytic Stability of Polyurethane Applied to Vehicle Suspension Components - Rigotti, Mateus; Bishoff, Eveline; Simon, Douglas Alexandre (Journal of Research Updates in Polymer Science, 2020)
Process parameters such as temperature and humidity, as well as formulation are the key factors in the manufacture of a polymeric component through a polyurethane prepolymer. These define the reaction kinetics, bonding and the resulting chemical interactions which determine the final characteristics of the material. One of the expected skills of polyurethane, when applied to components used in contact with water, is hydrolysis resistance. Consequently this research focused on exposure of a polymerized TDI (toluene diisocyanate) polyether polyurethane to different proportions of the curing agent, MOCA (4,4’-methylene-bis), in an environment susceptible to reactions with water at 70 °C. In this case, this material is applied in the manufacture of coil spring solid axle with trailing arms and Panhard rod suspension bushings. Mechanical tests and DSC (differential scanning calorimetry), TGA (thermogravimetry) and FT-IR (Fourier transform infrared) evaluations of the samples and prepolymer are conducted for the characterization of the different formulations, showing the negative relationship of the curing agent proportion parameters with the hydrolysis resistance. Here depolymerization of urethane and ether groups, as well as lower retention of yield stress are verified. These findings can subsidize developing predictive models for performance and lifetime of polyurethanes.